ECO-LABELING AS A TOOL FOR SUSTAINABLE DEVELOPMENT OF THE TEXTILE INDUSTRY - PAKHOLIUK, OLENA; PEREDRIY, OKSANA; DZYUBINSKIY, ANDRIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the environmental and social challenges of the textile and apparel industry, including the impact of clothing production on natural resource consumption, greenhouse gas emissions, the use of chemicals, and labor conditions. The complexity of assessing the sustainability of textile products is analyzed, considering the multi-level production chain and the low level of consumer awareness. Particular attention is given to the role of labeling as a tool for informing consumers and promoting responsible consumption. The classification of eco-labels according to ISO standards is presented, along with examples of well-known international standards (GOTS, EU Ecolabel, Nordic Swan, Blue Angel), and issues related to the multiplicity of labeling schemes and the risk of greenwashing are highlighted. The article also outlines prospects for improving labeling systems through the harmonization of requirements, the expansion of informational content, and the implementation of the Product Environmental Footprint (PEF) methodology. Eco-labeling and social labeling serve as important tools for fostering transparency and trust in the industry, as they provide consumers with information, encourage responsible choices, and can act as a catalyst for sustainable practices among producers. Further advancement can be achieved through standardization, international harmonization, and the adoption of comprehensive methodologies for assessing the environmental footprint of products. Enhancing the informational content of labels, improving their credibility, and ensuring greater clarity for consumers may serve as a foundation for the development of effective circular economy models in the textile industry and for mitigating the adverse impacts on both the environment and society. It is concluded that the development of effective labeling schemes can serve as a key factor in promoting circular economy models and reducing the negative environmental and social impacts of the textile industry.